Examining the Role of Child Protection Services in Domestic Violence Cases: Lessons Learned from Tragedies - Olszowy, Laura (Journal of family violence, 2021)
Exposure to domestic violence (DV) reports account for a significant portion of child welfare cases. However, there is a lack of resources for specifically working with cases that present a high-risk for lethality. The present study examined the involvement of child protection services (CPS) prior to domestic homicide cases. A retrospective case analysis was conducted utilizing cases reviewed by a domestic violence death review committee in Ontario, Canada. The study also examined the recommendations made by the committee to the child welfare sector. Overall, less than one-quarter of the homicide cases with children in the family system had CPS involvement. There were no differences in the presence of CPS involvement in cases where children were killed compared to cases where children were not killed. CPS-involved cases had significantly more risk factors and the family was involved with significantly more agencies overall. Recommendations directed to the child welfare sector highlighted the need for enhanced ongoing service provision to promote safety and hold perpetrators accountable, specialized DV training, and increased cross-sector collaboration. The child protection sector plays a critical role in assessing and managing risk in DV cases and preventing tragedies. The findings stress the importance of multi-disciplinary collaborations, and specialized ongoing training in engaging perpetrators and managing risk.